CONVERGENCE OF GREEN ECONOMY AND SUSTAINABLE DEVELOPMENT GOALS (SDGS) ECOLOGICAL FOOTPRINT STUDY IN THE TOURISM SECTOR OF BANYUWANGI - Inud Danis Ikhwan Meranti; Muhammad Syahrul Hidayat (FORPIM PTKIS ZONA TAPAL KUDA, 2026)
Environmental issues and social inequality have spurred the emergence of two major global agendas: the Green economy and the Sustainable Development Goals (SDGs). However, their implementation at the local level often runs parallel and lacks synergistic integration. This study examines the convergence of the Green economy and the Sustainable Development Goals (SDGs) in the tourism sector of Banyuwangi Regency through an ecological footprint study. The main issue addressed is the increasing ecological pressure due to rapid tourism growth, which has the potential to exceed environmental carrying capacity if not managed sustainably. The research focuses on assessing the ecological sustainability of the tourism sector and analyzing the extent to which its management aligns with green economy principles and relevant SDGs. This study employs a descriptive-interpretative qualitative approach, with data collected through interviews, observations, and document analysis. The findings indicate that tourism activities have exerted significant pressure on water and energy resources and generated substantial waste, particularly in nature-based tourism destinations. Although the Banyuwangi Regency Government has demonstrated commitment through policies such as the Clean Tourism Movement (GWB) and collaborations for renewable energy, which align with several SDGs, the implementation of sustainability principles remains uneven and partial. In conclusion, the convergence of the Green economy and SDGs in Banyuwangi is progressing incrementally but is not yet fully grounded in quantitative ecological footprint measurement. Therefore, standardizing environmental management and enhancing the capacity of all stakeholders are necessary to achieve truly sustainable tourism.